PENGEMBANGAN ALAT PERAGA ELEKTRONIKA PADA MATERI RANGKAIAN ARUS BOLAK-BALIK (ALTERNATING CURRENT) SEBAGAI MEDIA PEMBELAJARAN - Qorny, Rafita Al; Harjati, Purwiro; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2020)
Abstract: Researchers have conducted research on the development of electronic props in the AC current circuit material. This development research is research that aims to improve existing products. The purpose of this research and development is to determine the level of the feasibility of electronic props on the material of AC current circuits that are developed as learning media and to find out the respondent's response to electronic props on the material of AC current circuits developed. The research method uses Research and Development / R & D with the ADDIE development model which consists of Analysis (analysis), Design (design), Development (development), Implementation (implementation) and Evaluation (evaluation) stages. The analysis phase is to see the condition of the existing equipment. The Design Stage is designing the props that will be developed. The Development Phase is to develop by conducting expert validation. The implementation phase is to do a small group trial and evaluation stage, which is to repair electronic teaching aids in the material of AC current circuits developed. The results of research on electronic props media on the material of alternating current circuits are very feasible. Based on the results of the analysis of the assessment of media experts on electronic props on the material alternating current series obtained an average percentage of 82% with very decent criteria. Assessment of material experts obtained an average percentage of 81% with very reasonable criteria. The results of the student response questionnaire obtained a percentage of 89% with very agree criteria. Based on the results of the discussion regarding the development of electronic props in the AC current circuit material, it can be concluded that the teaching aids developed are very suitable for use as learning media. Suggestion, the use of electronic props on AC current circuit material developed for further research is expected to increase student interest and provide ease of understanding.